Budaya Populer Jepang Sebagai Instrumen Diplomasi Jepang dan Pengaruhnya Terhadap Komunitas-Komunitas di Indonesia - Aulia Amalina (Department of International Relations, Universitas Andalas)
Everystates in the world needs others to achieve its national interest and to get what its want is needed a power. One of kinds of power is called soft power that is using soft and unforce stuffs. One of kinds of this stuff is populer culture. Popular culture is used as one of the important diplomcy’s instrument by a state to achieve its interest. Japan as one of the states which is using its populer culture as diplomacy’s intrument. Japan uses its popularity to attract the world especially the young people. Its popularity also occurs in Indonesia, which is Indonesian young people are accepting, liking, and using this culture. This research uses concepts soft power and popular culture diplomacy. This research also use methodology qualitative research which is using Focus Group Discussion, indepht interview, and other resources to collect some datas. There are some conclusion of this research. First, the soft power is really exist in Japan’s popular culture diplomacy that makes tendency to consume japan’s products by young people in Indonesia. Then, it also impact to Japan’s image and position in politics and education by young people in Indonesia.